The Occult Dimension of Nazism: Magic, Mysticism, and Millenarian Expectations in the Third Reich - Asimiadis, Dionisis (Mos Historicus: A Critical Review of European History, 2025)
This paper examines the metaphysical dimension of Nazi Germany, analyzing the role of magic, mysticism, and millenarian beliefs in the Third Reich. It focuses on the influence of occult organizations and the connection between Nazism and German esotericism. The article explores the millenarian narrative promoted by Hitler, depicting his regime as the culmination of Aryan historical evolution. Furthermore, it analyzes the cult of the leader, the use of rituals and symbols, and their impact on Nazi propaganda and social cohesion. The study highlights the significance of these elements in understanding Nazi ideology and its influence on German society.